2017
DOI: 10.1088/1361-648x/aa73bb
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of the Shastry-Sutherland Kondo lattice model with classical localized spins: a variational calculation study

Abstract: Abstract. We study the Shastry-Sutherland Kondo lattice model with additional Dzyaloshinskii-Moriya (DM) interactions, exploring the possible magnetic phases in its multi-dimensional parameter space. Treating the local moments as classical spins and using a variational ansatz, we identify the parameter ranges over which various common magnetic orderings are potentially stabilized. Our results reveal that the competing interactions result in a heightened susceptibility towards a wide range of spin configuration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…We also note that the Dzyaloshinskii-Moriya interaction plays an important role for the Kondo effect and magnetic order at the interface between different materials. Theoretical research in this direction appears to be ongoing [121,122], but the impact on the f -electron superlattice is not clear at the moment.…”
Section: Discussionmentioning
confidence: 99%
“…We also note that the Dzyaloshinskii-Moriya interaction plays an important role for the Kondo effect and magnetic order at the interface between different materials. Theoretical research in this direction appears to be ongoing [121,122], but the impact on the f -electron superlattice is not clear at the moment.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the use of an external Zeeman field enhances the possibility of having noncoplanar phases significantly. Previously, we have shown that the Kondo lattice model on the SS lattice exhibits noncoplanar and noncollinear ground states over a wide range of parameters [46][47][48]. In this work, we aim to thoroughly study the effect of all the competing interactions in stabilizing the noncoplanar phases and investigate the transport properties of itinerant electrons on this lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Since DMI is ubiquitous in all of these materials, it is natural to supplement the canonical SS model with DMI. This results in an even richer variety of magnetic orderings including colinear, coplanar and non-coplanar spin configurations, several of which host topological magnons [17,36]. Previous studies of topological magnons for the SS lattice were restricted to the dimer [37] and the ferro-magnetic phases [38].…”
Section: Introductionmentioning
confidence: 99%